The effect of high-heeled shoe design on lower extremity kinetics, kinematics, and electromyography. (1st January 2012) - Eltoukhy, Moataz; Ozkaramanli, Deger; Asfour, Shihab
Many studies have investigated the differences in gait patterns with increasing heel height. The purpose of this study was to study the differences in gait patterns when wearing two high-heeled shoes (9 cm) deigns versus barefoot. Changes in lower extremity kinetics, kinematics and integrated electromyography (IEMG) were explored on 15 female college students (19–31 years). Increased vertical ground reaction forces during both early and late stance were recorded when wearing high-heeled shoes. Also, an increase in the IEMG values of soleus and lateral head of the gastrocnemius muscles were noted during stance, while medial head of the gastrocnemius EMG values decreased in both types of high-heeled shoes. IEMG of tibialis anterior was also decreased throughout swing phase due to more plantar flexed foot position.